The Experimental Study of the Effect of Cooling Pad Surface Shape on Passive Cooling Performance - Diana, Lohdy; Safitra, Arrad Ghani; Ariwibowo, Teguh Hady; Riyantoni, Ricko Guntur; Islam, Saiful; Prasetyo, Muhammad Fandi Setiawan Cahyono (invotek, 2024)
Climate change causes the air conditions inside buildings to increase in temperature. This causes the demand for cooling processes to increase every year. The use of cooling equipment currently requires quite a lot of electricity costs and produces CO2 emissions. The experimental study of the effect of cooling pad surface shape on passive cooling performance to produce a cooling device that is economical and environmentally friendly. The variations of the cooling pad surface were sinusoidal wave and triangular wave. The method was experiments carried out in the laboratory to control environmental conditions. The test results showed that the sinusoidal wave variation had a temperature drop of 1.1 °C lower than the triangular wave. The sinusoidal wave variation has 5% lower relative air humidity than triangular wave variation but air humidity for both variations had increased. Meanwhile, the use of silica sand could not reduce air humidity, it was because of the sum of sand that was used.